Cross-Cultural Digital Information-Seeking Experiences: The Case of Saudi Arabian Female International Students - Binsahl, Haifa; Chang, Shanton; Bosua, Rachelle (Journal of International Students, 2020)
The number of Saudi female international students (SFISs) pursuing higher degrees in Western countries has increased dramatically. Many are faced with unusual challenges, especially acting without a male’s permission, interacting with males, and using an open, free Internet. This article proposes that SFISs experience a “digital shift” whereby their cultural, educational, and digital backgrounds impact their information-seeking behavior in Australia. The study used a qualitative interpretivist methodology, interviewing a diverse group of SFISs studying in Australia, to better understand this impact on their everyday information needs and use of information sources. Findings indicate that SFISs’ imperfect online search skills, exacerbated by English language deficiency, increase their challenges. Recommendations for supporting SFISs are offered for institutions and service providers.